HUBUNGAN ANTARA KEPUASAN DENGAN KESETIAAN PASIEN (SURVEY PADA PASIEN BAGIAN JANTUNG RUMAH SAKIT INTERNASIONAL BINTARO TANGERANG) - Henry Eryanto (Jurnal Ilmiah Econosains, 2013)
ABSTRACTThis research was airned at describing connections between: 1) The Quality of Services to the Patient Loyalty, 2) The Satisfaction, all together, to the patient loyalty. This study was held in the Bintaro International Hospital, Tangerang. The method of research is survey method. The population consist of all internal disease patients of Bintaro International Hospital, Tangerang. Sample of research are 40 patients which were taken by random sampling method. The result of research, that the service quality and the patient saticfaction themselves or all together, giving significant result toward the patient loyalty. The attitude towards the improvement quality of services, and patient satisfaction need to be trained for the employees of Bintaro International Hospital. This matter cannot be separated from the employees recruitment. Specifically for the best services for their patients, besides that matters the hospital management must be improved their tools and equipment that they’re used, and would be hold the trainings for their employees.Keywords: quality of services, patient loyalty, satisfaction,